ENVIRONMENTAL FACTORS AND RESPIRATORY DISEASES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Respiratory diseases are among the leading causes of morbidity and mortality worldwide. Environmental factors such as air pollution, occupational exposures, and climate conditions play a crucial role in the development and exacerbation of respiratory disorders. This article reviews current evidence on the relationship between environmental exposures and respiratory health, highlighting statistical data on the prevalence of respiratory diseases in polluted urban areas and regions affected by environmental hazards. Strategies for prevention and mitigation of these risks are also discussed.